Neo-villeiny and the service sector: the case of hyper flexible and precarious work in fitness centres - Harvey, Geraint; Rhodes, Carl; Vachhani, Sheena J; Williams, Karen (Work, employment and society, 2017)
This article presents data from a comprehensive study of hyper flexible and precarious work in the service sector. A series of interviews were conducted with self-employed personal trainers along with more than 200 hours of participant observation within fitness centres in the UK. Analysis of the data reveals a new form of hyper flexible and precarious work that is labelled neo-villeiny in this article. Neo-villeiny is characterized by four features: bondage to the organization; payment of rent to the organization; no guarantee of any income; and extensive unpaid and speculative work that is highly beneficial to the organization. The neo-villeiny of the self-employed personal trainer offers the fitness centre all of the benefits associated with hyper flexible work, but also mitigates the detrimental outcomes associated with precarious work. The article considers the potential for adoption of this new form of hyper flexible and precarious work across the broader service sector.